Employment Status of Sorsogon State College Castilla Campus Graduates From Year 2013-2017 - Milagros Ebuenga; Rochele Aragon; Achilles Honasan; Perla Fortin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study aimed to determine the Personal Profile and employment status of Bachelor of Science in Agriculture, Bachelor of Science in Agricultural Development, Bachelor in Agricultural Technology and Bachelor of Science in Veterinary Technology graduates from 2013-2017 of SSC Castilla Campus; determine the performance of graduates towards work; find out the problems met in line with their jobs; and recommend measures to address the problems towards employment. This is a descriptive study and used documentary analysis, survey questionnaire and individual interview. The respondents were the graduates of the four programs from 2013-2017. Samples were determined using the Paguso formula. Results showed that 52.72% of the graduates of the four programs are female, 60.25% of them are married and their age are ranges from 21-30 years old; graduates of BSA took the licensure examinations and 53.22% of them are license agriculturists while12.90% are license teachers. For BAT, 40% of them are licensed agriculturists while there are 11.11% license teachers. For BSAD, 71.43% are licensed teachers and there are 2.86% licensed agriculturists. The BSVT is a non-board program but there are 3.22% took an extra effort to qualify for the Licensure exam for teachers; It was noted that 97.91% of the graduates are employed while 2.09% are self-employed.